Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and fibromyalgia: PR3-versus MPO-ANCA-associated vasculitis, an exploratory cross-sectional studyResearch in context - Charmaine van Eeden; Naima Mohazab; Desiree Redmond; Elaine Yacyshyn; Alison Clifford; Anthony S. Russell; Mohammed S. Osman; Jan Willem Cohen Tervaert (Elsevier, 2023)
Summary: Background: Persistent fatigue is a common complaint in ANCA-vasculitis (AAV) patients and has a profound impact on patient's quality of life. The symptoms associated with this fatigue mirror those found in patients with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and fibromyalgia. Etiologic and pathophysiologic differences exist between PR3- and MPO-ANCA disease, yet differences in their fatigue manifestations have not been well researched. We compared fatigue and its associations in healthy controls, AAV patients and fibromyalgia controls. Methods: The Canadian consensus criteria were used for ME/CFS diagnosis, and American College of Rheumatology criteria for fibromyalgia diagnosis. Factors such as cognitive failure, depression, anxiety, and sleep disturbances were assessed by patient reported questionnaires. Clinical factors such as BVAS, vasculitis damage index, CRP and BMI were also collected. Findings: Our AAV cohort comprised 52 patients, with a mean age of 44.7 (20-79), 57% (30/52) of the patients were female. We found 51.9% (27/52) of patients fulfilled the diagnostic criteria for ME/CFS, with 37% (10/27) of those having comorbid fibromyalgia. Rates of fatigue were higher in MPO-ANCA patients, than in PR3-ANCA patients, and their symptoms were more similar to the fibromyalgia controls. Fatigue in PR3-ANCA patients was related to inflammatory markers. These differences may be due to the varied pathophysiology of the PR3- and MPO-ANCA serotypes. Interpretation: A large proportion of AAV patients suffer from debilitating fatigue consequential enough to meet the diagnostic criteria for ME/CFS. Fatigue associations were not the same between PR3- and MPO-ANCA patients, suggesting that the underlying mechanisms may be different. Future studies should consider ANCA serotype, as further research may inform different clinical treatment strategies for AAV patients suffering from ME/CFS. Funding: This manuscript was funded by the Dutch Kidney Foundation (17PhD01).